Tobacco point-of-sale displays in England: a snapshot survey of current practices. Issue 4 (14th May 2010) - Rooke, Catriona; Cheeseman, Hazel; Dockrell, Martin; Millward, Deborah; Sandford, Amanda
Abstract : Background: Tobacco displays at the point of sale (PoS) are an important means for the tobacco industry to communicate with consumers. With regulations prohibiting PoS displays recently having come into force in Ireland, passed into law in England, Wales and Northern Ireland and some Australian states, and being considered in New Zealand, Finland and Brazil, this is an increasingly important issue. This study explores the nature of displays, the extent to which they are tobacco industry funded, and the relation between the tobacco companies and retailers. Methods: Three areas were chosen to gain a snapshot of PoS displays in England. Over 100 retailers were visited, with interviews taking place on site. Information was gathered on the type and size of tobacco display, who was paying for the display, requirements and incentives, and visits by industry representatives. Results: The majority of retailers had gantries provided by tobacco companies. A minority of these were fitted with automated dispensers called retail vending machines. Attractive lighting and colour were often used to highlight particular products. Most retailers were being visited by industry representatives who checked displays. Some retailers also reported incentives offered to them for displaying products. Conclusions: The results suggest that the tobacco industry presence and control in the retail environment is significant. Tobacco companies overwhelmingly provided tobacco gantries in the shops surveyed and influenced displays through a combination of requirements and incentives. The extensive involvement of tobacco companies in providing and monitoring retail displays suggests the importance of implementing policies to end this form of advertising.